Chinese herbal injection for cardio-cerebrovascular disease: Overview and challenges - Huajuan, Jiang; Xulong, Huang; Bin, Xian; Yue, Wang; Yongfeng, Zhou; Chaoxiang, Ren; Jin, Pei (Frontiers in Pharmacology, 2023)
Cardio-cerebrovascular diseases are the leading cause of death worldwide and there is currently no optimal treatment plan. Chinese herbal medicine injection (CHI) is obtained by combining traditional Chinese medicine (TCM) theory and modern production technology. It retains some characteristics of TCM while adding injection characteristics. CHI has played an important role in the treatment of critical diseases, especially cardio-cerebrovascular diseases, and has shown unique therapeutic advantages. TCMs that promote blood circulation and remove blood stasis, such as Salvia miltiorrhiza, Carthami flos, Panax notoginseng, and Chuanxiong rhizoma, account for a large proportion of CHIs of cardio-cerebrovascular disease. CHI is used to treat cardio-cerebrovascular diseases and has potential pharmacological activities such as anti-platelet aggregation, anti-inflammatory, anti-fibrosis, and anti-apoptosis. However, CHIs have changed the traditional method of administering TCMs, and the drugs directly enter the bloodstream, which may produce new pharmacological effects or adverse reactions. This article summarizes the clinical application, pharmacological effects, and mechanism of action of different varieties of CHIs commonly used in the treatment of cardio-cerebrovascular diseases, analyzes the causes of adverse reactions, and proposes suggestions for rational drug use and pharmaceutical care methods to provide a reference for the rational application of CHIs for cardio-cerebrovascular diseases.